Effective Optimization of High Voltage Solid‐State Lithium Batteries by Using Poly(ethylene oxide)‐Based Polymer Electrolyte with Semi‐Interpenetrating Network. (23rd August 2020) - Homann, Gerrit; Stolz, Lukas; Neuhaus, Kerstin; Winter, Martin; Kasnatscheew, Johannes
Abstract: Solid polymer electrolytes (SPEs) are promising candidates for the realization of lithium metal batteries. However, the popular SPE based on poly(ethylene oxide) (PEO) reveals a "voltage noise"‐failure during charge, for example, with high energy/high voltage electrodes like LiNi0.6 Mn0.2 Co0.2 O2 (NMC622), which can be attributed to short‐circuits via penetrating Li dendrites. This failure disappears when integrating PEO‐based SPE in a semi interpenetrating network, which mainly consists of PEO units, as well. In this work, it is shown that this SPE allows performance improvement via elimination of the crystalline domains without significant sacrifice of mechanical integrity. Hence, a highly amorphous SPE can be obtained by a simple increase of plasticizing Li salts, which overall is beneficial, not only for the ionic conductivity, but also the homogeneity, while remaining mechanically stable and solid in its original shape even after storage at 60 °C for 7 days. These aspects are crucial for the performance of the modified SPE as they can suppress the failure‐causing Li dendrite penetration while the electrochemical aspects, that is, anodic stability, are rather unaffected by the modification and remain stable (4.6 V vs Li│Li + ). Overall, this optimized SPE enables stable cycling performance in NMC622│SPE│Li cells, even at 40 °C operation temperature. Abstract : Common linear poly(ethylene oxide) (PEO)‐based solid polymer electrolytes demonstrate a short‐circuit in high voltage lithium metal batteries with, for example, LiNi0.6 Mn0.2 Co0.2 O2 (NMC622), seen by a characteristic voltage noise. Incorporation of linear PEO in a PEO‐based semi‐interpenetrating network suppresses the deteriorating Li dendrite penetration and enables further optimization opportunities, which realizes good performance even at 40 °C.